Impact of shortened dental arch on oral health-related quality of life over a period of 10 years — A randomized controlled trial. (January 2019) - Reissmann, Daniel R.; Wolfart, Stefan; John, Mike T.; Marré, Birgit; Walter, Michael; Kern, Matthias; Kohal, Ralf; Nothdurft, Frank; Stark, Helmut; Schierz, Oliver; Wöstmann, Bernd; Hannak, Wolfgang; et al.
Abstract: Objectives: To compare oral health-related quality of life (OHRQoL) in patients with either molar replacement by partial removable dental prostheses (PRDP) or with restored shortened dental arches (SDA) over a period of 10 years. Methods: In this multi-center RCT, a consecutive sample of 215 patients with bilateral molar loss in at least one jaw was initially recruited in 14 prosthodontic departments. Of those patients, 150 could be randomly allocated to the treatment groups (SDA: n = 71; PRDP: n = 79), received the allocated treatment, and were available for follow-up assessments. OHRQoL was assessed using the 49-item version of the Oral Health Impact Profile (OHIP) before treatment (baseline) and at follow-ups after treatment (4–8 weeks and 6, 12, 24, 36, 48, 60, 96, and 120 months). To investigate the course of OHRQoL over time, we longitudinally modelled treatment and time effects using mixed-effects models. Results: OHRQoL substantially improved from baseline to first follow-up in both groups indicated by a mean decrease in OHIP scores of 20.0 points (95%-CI: 12.5–27.5). When compared to the SDA group, OHRQoL in the PRDP group was not significantly different (−0.6 OHIP points; 95%-CI: −7.1 to 5.9) during the study period when assuming a constant time effect. OHRQoL remained stable over the 10 years with a statistically insignificant time effect (p = 0.848). Conclusions: For patients requesting prosthodontic treatment for their lost molars, treatments with SDA or PRDP improve clinically relevantly OHRQoL and maintain it over a period of 10 years with no option being superior to the other. Clinical significance: Since there was no significant difference between the two treatment options over the observation period of 10 years, and since results have stayed stable over time, patients can be informed that both treatment concepts are equivalent concerning OHRQoL.